STIFFENING ARRANGEMENT OPTIMIZATION FOR RECTANGULAR SURFACE CONDENSERS BY PARAMETRIC FEM APPROACH - Sagar Kailas More; Susheel M.Magar (International Journal of Innovations in Engineering Research and Technology, 2021)
In a power plant condenser is most important equipment. This equipment uses number of sub-components like condenser upper exhaust neck, Condenser lower exhaust neck, main condenser, nozzles. Steam leaving from the turbine gets absorbed inside a condenser through a exhaust neck & steam gets condensed inside a condenser main body. Stiffening arrangements are provided to support the internal components of the condenser as well as to restrict their deformation and buckling. By using parametricfinite element method model we can achieve flexibility in a design changes and optimization. Here various sub components of rectangular surface condenser will get analyzed to optimize stiffener size. Response surface optimization along with design of experiment methodology will be used for stiffener optimization. This optimization will help to reduce obstruction to steam flow in condenser.